Slope stability analysis by using multiple shear strength model - Lim, Kim Ong (2013)
Rainfall-induced landslide is a condition where rain water infiltrates into slope causing additional load and loss of shear strength of soil mass and eventually triggers slope failure. It is difficult to determine by applying conventional slope stability method as the method normally ignores the role of matric suction in the unsaturated zone existed above groundwater level. Suction has a strong influence on shear strength behavior where most of the rainfall-induced slopes failure occurred within unsaturated zone. In this study, three different shear strength models, namely Terzaghi (1936), Fredlund & Rahardjo (1978) and Md. Noor & Anderson (2006) are used in slope stability analysis for a parametric study subjected to different rainfall infiltration depth. This parametric study was done to identify the trend of the each model. Factor of safety was calculated and further discussed. Md. Noor & Anderson shear strength model gives a more critical and reliable stability factor with water infiltration compared to Fredlund & Rahardjo model. Terzaghi model which neglected soil suction give a lowest factor of safety and deep type of failure